2014
DOI: 10.1111/clr.12514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fixed implant‐supported prostheses, removable implant‐supported prostheses, and complete dentures: patient satisfaction and oral health‐related quality of life

Abstract: Although further research is still needed, prosthetic treatments may provide superior OHRQoL for fully edentulous patients. In particular, both the FP and RP treatments provided significantly greater improvement of OHRQoL and patient satisfaction than the CD treatment. Reliable information of OHRQoL and patient satisfaction helps experts and patients choose the best prosthetic treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 30 publications
4
97
0
8
Order By: Relevance
“…Only 6% demonstrated a reliable improvement for T2–T3. This positive effect of an implant treatment on OHRQoL has been noted by several recent studies . Patients with a Kennedy III classification had a statistically significant higher OHIP score at intake (T1) and after 2 weeks of surgery (T2) than did patients with a Kennedy II classification.…”
Section: Discussionsupporting
confidence: 74%
“…Only 6% demonstrated a reliable improvement for T2–T3. This positive effect of an implant treatment on OHRQoL has been noted by several recent studies . Patients with a Kennedy III classification had a statistically significant higher OHIP score at intake (T1) and after 2 weeks of surgery (T2) than did patients with a Kennedy II classification.…”
Section: Discussionsupporting
confidence: 74%
“…The excellent results found in the present study could also be related to the good prosthesis stability as, on an average, each prosthesis was supported by four or more implants. Another study by Oh and colleagues confirmed that oral health‐related quality of life improved similarly for implant‐supported fixed prosthesis and for implant‐anchored overdentures as compared to removable dentures . The authors stressed the importance to focus on patient‐centred outcomes when choosing a treatment option.…”
Section: Discussionmentioning
confidence: 95%
“…1,2 Nonetheless, there are few studies assessing the Oral Health-Related Quality of Life (OHRQoL) of implant prosthesis wearers. [3][4][5][6] Although different generic scales have been used, 3,4,[7][8][9] specific questionnaires are preferred to measure the impact of implant prostheses on the OHRQoL. 5,6 In this respect, a new, short and precise index, called 'Quality of Life with ImplantProstheses (QoLIP-10)' 5,6 has recently been developed.…”
Section: Introductionmentioning
confidence: 99%